Kooperative Informationsinfrastrukturen als Chance und Herausforderung : Festschrift für Thomas Bürger zum 65. Geburtstag - Bonte, Achim; Rehnolt, Juliane (2018)
Cooperative information infrastructures as a chance and a challenge to this topic are the contributions to the Festschrift for Thomas Bürger on the occasion of his 65th birthday. More than 40 contributions by renowned scholars and librarians provide an up-to-date overview.